Swell and Consolidation Characteristics of Fiber Reinforced Cohesive Soil - Rajeena; S. P. Jeyapriya (Asian Journal of Engineering and Applied Technology, 2018)
Naturally occurring expansive clays show detrimental changes in volume when subjected to variation in water content. It leads to significant damages in foundations that are seated on these materials used for the construction in pavement, bridges especially in light weight buildings. The improvement could be in terms of reducing the swelling and differential settlement or increasing the shear strength of clayey soil. Reinforcing soil using fiber is one of the ground improvement techniques in which fibers are mixed randomly with the soil, in similar fashion to mixing with lime, cement or other additives. It eliminates the potential weak planes and maintains the strength isotropy by random reinforcement. The main objective of this study is to investigate the effect of synthetic polypropylene fibers on the swelling and consolidation characteristics of clay soil. The parameters considered for the study include the swelling pressure, swell potential and consolidation characteristics. Polypropylene fiber with aspect ratio (l/d) 12 is varied at 0%, 0.1%, 0.25%, 0.50% and 0.75% by dry weight of the soil is used as reinforcement. The swell potential(S%) and the swelling pressure(P) decreased with the addition of fiber. From the experimental results, 0.5% of polypropylene fiber is considered to be optimum. The results also revealed that the rate of heave formation is very less compared to that of unreinforced soil. From the consolidation test, it was observed that compression index, co efficient of compressibility and co efficient of volume change are 0.22, 0.8 mm2/N and 0.48mm2/N at the optimum fiber percentage.